النفس الإنسانية ومقاصد بنائها في القرآن الكريم: دراسة موضوعية - شوشة، حسام موسى محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2016)
The current study aims to discover the human soul and objectives of building it, and examine the concept of human soul and its various situations as mentioned in the Qur'an. The study clarifies the Qur'anic approach to protect the human soul from potential illusions and diseases by explaining some characters and diseases of human soul that are mentioned in the Qur'an. Then, the study investigates the concept, methods and features of Qur'anic approach to building human soul. Besides, the study explains the objectives of building human soul as stated in the Qur'an. The ultimate objective of the study is to preserve human soul from diseases before they occur. In order to achieve these objectives, the study employs inductive and deductive methods to collect verses and prophetic traditions to derive the Qur'anic purposes and manner in building human soul. The main findings are: 1. The human soul has a unique concept in the Qur'an as shown in “The underlying forces in the human body which is a complex good and bad emotions and stable instincts and tendencies and emotions which dynamics of this body at his disposal and Direction”, 2. There are various types of human soul, 3. Each type has its own conditions and different means to deal with it, 4. The Qur'an has set objectives (worship, educational, advocacy (Da'wah) and community) to build human soul, 5. There is a way for happiness as seen in “Act in accordance with Allah's orders to attain the true meaning of succession”, and 6. The Qur'an, as well as the Sunnah, has distinctive approaches to achieving happiness.